(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
We establish an estimate for the outer measure γ_I(T) and the inner measure β_I(T) of an operator T acting between some intermediate spaces constructed for n-tuples of Banach spaces. We also show that many operator ideals have the strong interpolation property for Sparr’s interpolation methods.